Роль ЮНЕСКО у збереженні нематеріальної культурної спадщини в Україні - Багіров, Вусал Елмас Огли (My University, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi.
Магістерська робота
Keywords: Міжнародні відносини, ЮНЕСКО, Україна